Antibacterial activity of Turmeric (Curcuma longa L.) essential oil against human pathogen using cell viability assay. - Balboa, Dexter Gicaro
Infectious diseases, aggravated by emergence and re-emergence of new diseases and development of antibiotic resistance, are still the leading cause of death worldwide. Thus, the search for compounds from plants to have novel antibiotic properties is vital. The present study aimed to determine the in vitro antibacterial activity of Curcuma longa L. varr Murcia rhizome essential oils. The essential oils were extracted by hydrodistillation and tested against Proteus vulgaris 1062, Staphylococcus saprophyticus 1798, Streptococcus mutans 10231, Enterococcus fecalis 1072, Escherichia coli 1634, Salmonella typhinurium 1328, Salmonella typhi 1756, Pseudomonas aeruginosa 1335, Klebsiella pneumonia 1754, and Enterobacter aerogenes 1145 using disc-diffusion assay and cell viability assay. GC-MS analysis shows that α-Phellandrene and eucalyptol are the characteristic component of the EO. Results show that Salmonella typhinurium, Escherichia coli, Enterococcus faecalis, Enterobacter aerogens, and Salmonella typhi are most susceptible (ZOI 13.5mm to 16.4mm; log reduction 4 to 5; % killed > 99.9%). Pseudomonas aeruginosa and Proteus vulgaris are less susceptible with ZOI 9mm to 11mm. Klebsiella pneumonia, Staphylococcus saprophyticus, and Streptococcus mutans are least susceptible as evidence by the absence of inhibition and low log reduction. The present study implies that turmeric essential oil has great potential in antibiotic drug discovery and can be used for therapeutic purposes. Further, the data suggests of the use of cell viability assay for future antibacterial studies of plant extracts.